Human NK Cell Subsets Redistribution in Pathological Conditions: A Role for CCR7 Receptor - Pesce, Silvia; Moretta, Lorenzo; Moretta, Alessandro; Marcenaro, Emanuela (Frontiers in Immunology, 2016)
Innate and adaptive immunity has evolved complex molecular mechanisms regulating immune cell migration to facilitate the dynamic cellular interactions required for its function involving the chemokines and their receptors. One important chemokine receptor in the immune system is represented by CCR7. Together with its ligands CCL19 and CCL21, this chemokine receptor controls different arrays of migratory events, both in innate and adaptive immunity, including homing of CD56bright NK cells, T cells and DCs to lymphoid compartments where T cell priming occurs. Only recently, a key role for CCR7 in promoting CD56dim NK cell migration towards lymphoid tissues has been described. Remarkably, this event can influence the shaping and polarization of adaptive T cell responses. In this review, we describe recent progress in understanding the mechanisms and the site where CD56dim KIR+ NK cells can acquire the capability to migrate towards lymph nodes. The emerging significance of this event in clinical transplantation is also discussed.